2020
DOI: 10.48550/arxiv.2005.05983
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geometric Approach to 3D Interfaces at Strong Coupling

Markus Dierigl,
Jonathan J. Heckman,
Thomas B. Rochais
et al.

Abstract: We study 4D systems in which parameters of the theory have position dependence in one spatial direction. In the limit where these parameters jump, this can lead to 3D interfaces supporting localized degrees of freedom. A priori, this sort of position dependence can occur at either weak or strong coupling. Demanding time-reversal invariance for U (1) gauge theories with a duality group Γ ⊂ SL(2, Z) leads to interfaces at strong coupling which are characterized by the real component of a modular curve specified … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 107 publications
(171 reference statements)
0
1
0
Order By: Relevance
“…F-theory models of elliptic fibrations possessing a global section have been analyzed. Recent studies of such models can be found, e.g., in[4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49]. F-theory model constructions where one or more U(1) factors are formed are discussed, for example, in[4,7,8,10,…”
mentioning
confidence: 99%
“…F-theory models of elliptic fibrations possessing a global section have been analyzed. Recent studies of such models can be found, e.g., in[4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49]. F-theory model constructions where one or more U(1) factors are formed are discussed, for example, in[4,7,8,10,…”
mentioning
confidence: 99%